Levels and trends of contraceptive prevalence and estimate of unmet need for family planning in Rwanda: Further analysis of the Rwanda Demographic and Health Surveys, 2000–2007/08 - Ayad, Mohamed; Hong, Rathavuth (DHS Further Analysis Reports No. 67, 2009)
Rwanda is the most densely populated country in Africa and one of the fastest growing countries in the region. The family planning program is among the government's planned goals and strategies for reducing poverty, developing the country and improving the health of the Rwandan population. This study presents levels, trends, and differentials in the use of contraception and estimates the level of unmet need for family planning among women of reproductive age. The use of contraception has increased substantially from 2000 to 2007-08 among women currently in union in Rwanda. From 2005 to 2007-08, contraceptive prevalence increased almost threefold from 13% to 36%. This increase is predominantly a result of an increase in the use of modern contraceptive methods. Women who are of prime reproductive age, have higher parity, are better educated, and live in urban and more highly developed areas (Kigali), are more likely than other women to use a contraceptive method. In 2007-08, the level of unmet need for family planning among women currently in union dropped, likely due to an increase in the use of contraception, particularly for the purpose of limiting births. In addition, the components of unmet need have changed as more women currently need family planning for limiting births than for spacing than in 2000 and 2005.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report presents findings from a further analysis study undertaken as part of the follow-up to the 2007-08 Rwanda Interim Demographic and Health Survey (RIDHS). ICF Macro provided technical assistance for the project. Funding was provided by the United States Agency for International Development (USAID) under the terms of Contract No. HRN-C-00-97-00019-00. The opinions expressed herein are those of the authors and do not necessarily reflect the views of the USAID. This report is part of the MEASURE DHS program, which is designed to collect, analyze, and disseminate data on fertility, family planning, maternal and child health, nutrition, and HIV/AIDS. Information about the DHS program can be obtained from MEASURE DHS, ORC Macro, 11785 Beltsville Drive, Suite 300, Calverton, MD, USA (Telephone: 301-572-0200; Fax: 301-572-0999; E-mail: reports@orcmacro.com; Internet: http://www.measuredhs.com).